Characterization of microplastic pollution in coastal sediments of Vietnam - Le, Xuan Thanh Thao; Duc Long, Huynh; Do, Van Manh (Vietnam Journal of Marine Science and Technology, 2026)
Microplastics have increasingly been recognized as an emerging pollutant and have attracted considerable global scientific attention due to their potential impacts on ecosystems and human health. However, information on microplastics in Vietnam’s marine environment remains limited, fragmented and lacking systematic synthesis. This study provides a systematic review of peer-reviewed publications from 2020 to 2024 that investigated microplastics in coastal marine sediments across Vietnam. Reported concentrations ranged from 0 to 29,232 microplastics/kg (MPs/kg), with mean values ranging between 2.82 and 10,830 MPs/kg. Secondary microplastics were the dominant type, primarily occurring as fibers and fragments. A total of 32 polymer types were identified, among which polyamide (PA), polypropylene (PP), polystyrene (PS) and polyethylene (PE) were the most frequently detected. These findings provide a comprehensive overview of the current status of microplastic pollution in Vietnam’s coastal waters, revealing methodological inconsistencies and underscoring the urgent need to standardize future investigation protocols.